2020
DOI: 10.1302/0301-620x.102b9.bjj-2020-1147.r1
|View full text |Cite
|
Sign up to set email alerts
|

The theoretical mortality risk of an asymptomatic patient with a negative SARS-CoV-2 test developing COVID-19 following elective orthopaedic surgery

Abstract: Aims The risk to patients and healthcare workers of resuming elective orthopaedic surgery following the peak of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has been difficult to quantify. This has prompted governing bodies to adopt a cautious approach that may be impractical and financially unsustainable. The lack of evidence has made it impossible for surgeons to give patients an informed perspective of the consequences of elective surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 24 publications
4
34
1
Order By: Relevance
“…3 Routine swabbing may have a false negative rate of around 30%, meaning that at times it may falsely reassure, while as prevalence falls the proportion of positive tests that are true positives becomes increasingly minuscule. 17 The data from this study support performing day case upper limb surgery not requiring GA without routine SARS-CoV-2 testing in healthcare settings in which patient groups can be kept physically separate. This would enable those patients being treated under local or regional anaesthetic to remain distant from other patients in whom the potential implications of contracting SARS-CoV-2 would be likely to be more serious, for example, this may be via the use of a dedicated minor operations facility.…”
Section: Discussionsupporting
confidence: 56%
“…3 Routine swabbing may have a false negative rate of around 30%, meaning that at times it may falsely reassure, while as prevalence falls the proportion of positive tests that are true positives becomes increasingly minuscule. 17 The data from this study support performing day case upper limb surgery not requiring GA without routine SARS-CoV-2 testing in healthcare settings in which patient groups can be kept physically separate. This would enable those patients being treated under local or regional anaesthetic to remain distant from other patients in whom the potential implications of contracting SARS-CoV-2 would be likely to be more serious, for example, this may be via the use of a dedicated minor operations facility.…”
Section: Discussionsupporting
confidence: 56%
“…As lockdown measures in the UK and globally eases and the incidence of trauma returns to pre-lockdown trends, it is imperative that we understand the true increased risk of mortality in the acute trauma patient during the COVID-19 era. A recent publication by Kader et al 16 has suggested that the rate of mortality from COVID-19 for elective Orthopaedic patients is low; yet this is the first nationwide study to quantify mortality risk for trauma patients. Trauma procedures due to the nature of the injuries are necessary and time-critical, and nobody can afford to postpone trauma care even during a global pandemic 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In the worst-case scenario, asymptomatic but infected patients could become super spreaders, which may generate infection clusters in the hospital. In a recent calculation in the United Kingdom, the risk of patients with an undetected SARS-CoV-2 infection being inadvertently admitted for elective orthopaedic surgery was relatively low (0.07%, 1 in 1400) [21]; however, the best efforts should be taken to decrease this possibility. The self-quarantine programme is beneficial in decreasing the possibility of infection in patients scheduled to undergo elective surgery if all patients strictly obey the rules.…”
Section: Discussionmentioning
confidence: 99%